Applied Adhesion Science - de Barros, Silvio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Applied Adhesion Science focuses on practical applications of adhesives, with special emphasis in fields such as oil industry, aerospace and biomedicine. Topics related to the phenomena of adhesion and the application of adhesive materials are welcome, especially in biomedical areas such as adhesive dentistry. Both theoretical and experimental works are considered for publication. Applied Adhesion Science is a peer-reviewed open access journal published under the SpringerOpen brand. The journal's open access policy offers a fast publication workflow whilst maintaining rigorous peer review process.
Keywords: Materials science; Mechanical engineering; Biomaterials; Materials -- Surfaces; Thin films; Materials Science; Surfaces and Interfaces, Thin Films; Mechanical Engineering; Biomaterials